(untitled) (Libellarium: journal for research in the field of information and related sciences, 2012)
The aim of this paper is to investigate and present the activities of the Public Library in Celje during German occupation during World War II. The research is based on a survey of archival sources – relevant documents are available in Celje Historical Arcives (Zgodovinski arhiv Celje – ZAC). The article is divided in two parts, the first one presenting the condition of librarianship in Nazi Germany in general, and the second one focusing on a case study: the conditions of librarianship in occupied Slovenian city of Celje. The city was an important administrative, commercial, industrial, traffic and educational centre in the area of Styria during the occupation. Its library operated according to standards and models applied to libraries in Germany. This was reflected in the overall library operation: selection and processing of material, layout, employee selection and work with users. Public libraries were founded by individual municipalities or groups of municipalities, which took care of the operation of libraries. Special government advisory centres (Staatliche Volksbuechereistelle) provided library’s additional materials. Consequently, libraries played an important role in dissemination of the German language and culture in new border areas, which was regarded as their major aim. War conditions did not deter users from visiting libraries and employee complaints about the lack of financial means were not recorded. Towards the end of the war only the lack of paper was noticed.